Pengembangan Aplikasi Relaksasi Autogenik Berbasis Android Terhadap Tingkat Stres Pada Pasien Gagal Jantung - Dianita, Eka Mei; Sukartini, Tintin; Pratiwi, Ika Nur (Universitas Tribhuwana Tunggadewi, 2023)
Heart disease become a leading cause of death globally. Heart failure is also a problem in Indonesia. Stress-induced smoking, lessening physical activity, diet habits, and medication non-adherence affected morbidity and mortality among heart failure patients. In the current era of digitalization, smartphones become a communication tool and source of information that are easily accessible to the public due to time, effort, and cost efficiency. This study aims to develop an Android-based autogenic relaxation intervention application to reduce stress levels. A research and development study design was used. There are three steps, the exploration of stress levels, evaluation of stress management by nurses, application development with focus group discussions and expert consultations; and the feasibility test. In stage 1, about 109 patients were assessed using a perceived stress scale questionnaire and interview sheet. In stage 2, 10 patients were assessed using the system usability scale questionnaire. Descriptive analysis was used. The result showed lifestyle changes contributing to stress levels. Stress management by nurses resulting moderates stress levels (78.9%). The Android-based application develops a menu of autogenic relaxation instructions, exercises, health education, and level evaluation. The results of the feasibility test received good acceptance from users. The Android-based autogenic relaxation applications can reduce stress levels in heart failure patients. Another study to determine the effect of autogenic relaxation applications in reducing stress levels in heart failure patients is further recommended.